Effect of variable compression ratio and equivalence ratio on performance, combustion and emission of hydrogen port injection SI engine. (15th January 2022) - Pandey, Jayashish Kumar; Kumar, G.N.
Abstract: The present study includes an experimental investigation of the performance, combustion, and emission parameters of a hydrogen port fueled SI engine under wide-open throttle. The compression ratio (CR) is varied from 10 to 15, equivalence ratio (φ) from 0.4 to 1.0, and speed from 1400RPM to 1800RPM. The ignition timing is maintained at 20° before the top dead center. The brake thermal efficiency increases by nearly 10% from CR10 to CR15, and it also increased by 13.7% by changing φ from 0.4 to 0.9. Similarly, BP increases in the same fashion. The combustion enhances with an increase in peak pressure by increasing CR from 10 to 15 and φ from 0.4 to 0.9; however, φ 1.0 exhibits a negative trend. However, the NOX emission increases continuously with CR and φ, and so as the exhaust gas temperature. The carbon-based emissions are negligible, and volumetric efficiency decreases with φ and increases with CR. Highlights: High heat content and carbonless nature are key factors of hydrogen as a fuel. High laminar flame speed and low ignition energy provide suitability in SI engines. Increasing compression ratio improves lean combustion characteristics of hydrogen. Equivalence ratio 0.7, exhibit better brake thermal efficiency and brake power. Carbonless burning of hydrogen produces negligible CO, CO2, and HC emissions.